CCR3 Blockade Attenuates Eosinophilic Ileitis and Associated Remodeling - Masterson, Joanne C. (American Society for Investigative Pathology, 2011)
Intestinal remodeling and stricture formation is a complication of inflammatory bowel disease (IBD) that often requires surgical intervention. Although eosinophils are associated with mucosal remodeling in other organs and are increased in IBD tissues, their role in IBD-associated remodeling is unclear. Histological and molecular features of ileitis and remodeling were assessed using immunohistochemical, histomorphometric, flow cytometric, and molecular analysis (real-time RT-PCR) techniques in a murine model of chronic eosinophilic ileitis. Collagen protein was assessed by Sircol assay. Using a spontaneous eosinophilic Crohn's-like mouse model SAMP1/SkuSlc, we demonstrate an association between ileitis progression and remodeling over the course of 40 weeks. Mucosal and submucosal eosinophilia increased over the time course and correlated with increased histological inflammatory indices. Ileitis and remodeling increased over the 40 weeks, as did expression of fibronectin. CCR3-specific antibody-mediated reduction of eosinophils resulted in significant decrease in goblet cell hyperplasia, muscularis propria hypertrophy, villus blunting, and expression of inflammatory and remodeling genes, including fibronectin. Cellularity of local mesenteric lymph nodes, including T- and B-lymphocytes, was also significantly reduced. Thus, eosinophils participate in intestinal remodeling, supporting eosinophils as a novel therapeutic target.